Design, Development, and Evaluation of Nsaid Drug in Soft gel Dosage Form - Akash, Vemuri (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
All the pharmaceutical products formulated for systemic delivery through the oral route of administration irrespective of the mode of delivery immediate sustained or controlled release and the design of dosage forms (either solid dispersion or liquid), must be developed within the intrinsic characteristics of GI physiology, pharmacokinetics, pharmacodynamics, and formulation design is essential to achieve a systemic approach to the successful development of an oral pharmaceutical dosage form.